Antioxidant Enzyme Activity and Serum HSP70 Concentrations in Relation to Insulin Resistance and Lipid Profile in Lean and Overweight Young Men - Anna Lubkowska; Wioleta Dudzińska; Waldemar Pluta (MDPI AG, 2023)
Oxidants are generated by all cells during normal oxidative respiration, and as long as they are under the control of appropriate mechanisms, they act as intracellular signaling molecules participating in complex functions. Oxidative stress can also affect insulin levels in the body. The production of reactive oxygen species by-products can lead to insulin resistance. Heat shock proteins (70 kDa) protect cells from the damaging effects of heat shock but also oxidative stress. The aim of the study was to investigate the serum concentration of HSP70 in young, non-obese but overweight men (BMI ≤ 30 kg/m2) and to assess its association with the insulin resistance, lipid profile and antioxidant system of red blood cells. Fifty-seven young men were examined and divided into two groups: lean men (n = 30) and men overweight (n = 27). A statistically significant difference was observed in the BMI (p < 0.007), HSP70 concentration (p < 0.000), serum insulin concentration (p < 0.000), HOMA-IR (p < 0.0001), superoxide dismutase (p < 0.02) and glutathione peroxidase (p < 0.05) between the studied groups. There was a negative correlation between the concentration of HSP70 with the insulin level (r = −0.50; p < 0.0004) and with the HOMA-IR (r = −0.50; p < 0.0004). These changes were associated with an increase in the activity of antioxidant enzymes. Our findings suggest that measuring the extracellular concentration of HSP70 can be an important indicator in disorders of glucose homeostasis.